CRC Handbook of Thermoelectrics - Rowe, D.M.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Thermoelectrics is the science and technology associated with thermoelectric converters, that is, the generation of electrical power by the Seebeck effect and refrigeration by the Peltier effect. Thermoelectric generators are being used in increasing numbers to provide electrical power in medical, military, and deep space applications where combinations of their desirable properties outweigh their relatively high cost and low generating efficiency. In recent years there also has been an increase in the requirement for thermoelectric coolers (Peltier devices) for use in infrared detectors and in optical communications. Information on thermoelectrics is not readily available as it is widely scattered throughout the literature. The Handbook centralizes this information in a convenient format under a single cover.Sixty of the world's foremost authorities on thermoelectrics have contributed to this Handbook. It is comprised of fifty-five chapters, a number of which contain previously unpublished material. The contents are arranged in eight sections: general principles and theoretical considerations, material preparation, measurement of thermoelectric properties, thermoelectric materials, thermoelectric generation, generator applications, thermoelectric refrigeration, and applications of thermoelectric cooling.The CRC Handbook of Thermoelectrics has a broad-based scope. It will interest researchers, technologists, and manufacturers, as well as students and the well-informed, non-specialist reader.
Introduction, D.M. RoweGeneral Principles and Theoretical ConsiderationsThermoelectric Phenomena, D.D. PollockCoversion Efficiency and Figure-of-Merit, H.J. GoldsmidThermoelectric Transport Theory, C.M. BhandariOptimization of Carrier Concentration, C.M. Bhandari and D.M. RoweMinimizing the Thermal Conductivity, C.M. BhandariSelective Carrier Scattering in Thermoelectric Materials, Y.I. RavichThermomagnetic Phenomena, H.J. GoldsmidMaterial PreparationPreparation of Thermoelectric Materials from Melts, A. BorshchevskyPowder Metallurgy Techniques, A.N. ScovillePIES Method of Preparing Bismuth Alloys, T. Ohta and T. KajikawaPreparation of Thermoelectric Materials by Mechanical Alloying, B.A. Cook, J.L. Harringa, and S.H. HanPreparation of Thermoelectric Films, K. Matsubara, T. Koyanagi, K. Nagao, and K. KishimotoMeasurement of Thermoelectric PropertiesCalculation of Peltier Device Performance, R.J. BuistMeasurements of Electrical Properties, I.A. NishidaMeasurement of Thermal Properties, R. TaylorZ-Meters, H.H. Woodbury, L.M. Levinson, and S. LewandowskiMethodology for Testing Thermoelectric Materials and Devices, R.J. BuistThermoelectric MaterialsBismuth Telluride, Antimony Telluride, and Their Solid Solutions, H. Scherrer and S. ScherrerValence Band Structure and the Thermoelectric Figure-of-Merit of (Bi1-xSbx)Te3 Crystals, M. StordeurLead Telluride and Its Alloys, V. FanoProperties of the General Tags System, E.A. Skrabek and D.S. TrimmerThermoelectric Properties of Silicides, C.B. ViningPolycrystalline Iron Disilicide as a Thermoelectric Generator Material, U. Birkholz, E. Gross, and U. StohrerThermoelectric Properties of Anisotropic MnSi1.75 , V.K. ZaitsevLow Carrier Mobility Materials for Thermoelectric Applications, V.K. Zaitsev, S.A. Ktitorov, and M.I. FederovSemimetals as Materials for Thermoelectric Generators, M.I. Fedorov and V.K. ZaitsevSilicon Germanium, C.B. ViningRare Earth Compounds, B.J. Beaudry and K.A. Gschneidner, Jr.Thermoelectric Properties of High-Temperature Superconductors, M. Cassart and J.-P. IssiBoron Carbides, T.L. Aselage and D. EminThermoelectric Properties of Metallic Materials, A.T. Burkov and M.V. VedernikovNeutron Irradiation Damage in SiGe Alloys, J.W. VandersandeNew Materials and Performance Limits for Thermoelectric Cooling, G.A. SlackThermoelectric GenerationMiniature Semiconductor Thermoelectric Devices, D.M. RoweCommercially Available Generators, A.G. McNaughtonModular RTG Technology, R.F. HartmanPeltier Devices as Generators, G. Min and D.M. RoweCalculations of Generator Performance, M.H. CobbleGenerator ApplicationsTerrestrial Applications of Thermoelectric Generators, W.C. HallSpace Applications, G.L. BennettSP-100 Space Subsystems, J.F. MondtSafety Aspects of Thermoelectrics in Space, G.L. BennettLow-Temperature Heat Conversion, K. Matsuura and D.M. RoweThermoelectric RefrigerationIntroduction, H.J. GoldsmidModule Design and Fabrication, R. Marlow and E. BurkeCooling Thermoelements with Superconducting Leg, M.V. Vedernikov and V.L. KuznetsovApplications of Thermoelectric CoolingIntroduction, H.J. GoldsmidCommercial Peltier Modules, K.-I. UemuraThermoelectrically Cooled Radiation Detectors, L.I. AnatychukReliability of Peltier Coolers in Fiber-Optic Laser Packages, R.M. Redstall and R. StuddLaboratory Equipment, K.-I. UemuraLarge-Scale Cooling: Integrated Thermoelectric Element Technology, J.G. StockholmMedium-Scale Cooling: Thermoelectric Module Technology, J.G. StockholmModeling of Thermoelectric Cooling Systems, J.G. Stockholm.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Electronics / General; Thermoelectric materials; Electronic books